«Alguien le dice al Tango»: Borges, tango y milonga - Susti Gonzales, Alejandro Enrico (2023)
This article examines the relationship between the work of Jorge Luis Borges (1899-1986) and two musical genres that appeared in the Río de la Plata at the end of the Ninenteen century and the beginning of the Twentieh century: Tango and Milonga. Considering some of the essays and testimonies given by the author, I intend to understand the attraction that Tango produced in him as well as his project of founding a mythical and imaginary past, «a Tango Mithology», based on its referents and figures. Concerning Milonga, assuming his notes on the role of music, instrumentation, an interpretation, I examine the connection between la milonga and la payada in his work Para las seis cuerdas (1965), and the invention of an absolutely personal «milonga poetics». Finally, I include the testimonies of several important figures in the history of Tango to establish the role Borges in it.